Cyperus coonoorensis (Cyperaceae), a new species from the Nilgiri Biosphere Reserve, India - Viji, A. R.; Pandurangan, A. G.; Deepu, S.; Tucker, G. C. (Phytotaxa, 2015)
Cyperus coonoorensis sp. nov. (Cyperaceae) is described and illustrated as a new species from Nilgiri Biosphere Reserve, Western Ghats, India. A member of sect. Diffusi, the new species distinctly differs from related species, C. diffusus, by its long and stout rhizome, large inflorescence and number of florets and spikelets. A detailed description, phenology, illustration, colour plates, distribution and relevant notes are provided. A key to the sect. Diffusi in South Asia is also provided.